Different whole body HIIT protocols do not promote different muscle thickness and functional adaptations among healthy physically active subjects - Alexandre L. Evangelista; Júlio B. B. de Camargo; Roberta L. Rica; Luiz Carlos Carnevali Júnior; Gregg S. Mallett; Valentina Bullo; Marco Bergamin; Stefano Gobbo; Danilo S. Bocalini (Frontiers in Sports and Active Living)
IntroductionDespite robust evidence on the benefits of high intensity interval training using body weight (WB-HIIT), the effects of different training configurations on morpho-functional adaptations are still unclear. Therefore, the aim of the present study was to assess the effects of two distinct WB-HIIT protocols on morphological and general fitness adaptations in healthy active young individuals.MethodsThirty-four participants (22 males and 12 females) were randomly assigned to one of the following groups: 30 s of all-out effort interspersed with 10 s of passive recovery (G30 × 10, n = 17) or 40 s of an all-out effort interspersed with 20 s of passive recovery (G40 × 20, n = 17). Nine exercises were performed for both protocols, in two weekly sessions, during a 6-week intervention period. Morphological (ultrasound-derived muscle thickness of the vastus lateralis [MTVL]) and general fitness (muscle endurance and maximal oxygen consumption) assessments were performed at pre- and post-intervention moments.ResultsBoth training protocols elicited significant improvements in all dependent variables (p < 0.05), with no significant between-group differences.ConclusionRegardless of the training configuration, both WB-HIIT programs serve as time-efficient strategies to induce changes in muscle thickness of the vastus lateralis and functional adaptations in healthy, physically active young individuals.